Taxonomic identity of the enigmatic Western Australian fish species Stigmatonotus australis Peters, 1877 (Teleostei) - Gill, Anthony C. (Zootaxa, 2023)
The familial classification and specific identity of Stigmatonotus australis Peters, 1877 has been unresolved ever since its original description. Examination of a photograph and X-radiograph of the holotype confirms placement in the serranid subfamily Anthiadinae. It is further identified to the genus Hypoplectrodes Gill, 1862 and shown to represent a juvenile specimen of the species currently called H. cardinalis Allen & Randall, 1990. Character and other evidence supporting this conclusion are summarised, including discussion of apparently contradictory characters. Consequently, the following synonymisations are proposed: the family-group name Stigmatonotidae Whitley, 1954 with Anthiadides Poey, 1861, the generic name Stigmatonotus Peters, 1877 with Hypoplectrodes Gill, 1862, and the species name H. cardinalis Allen & Randall, 1990 with S. australis Peters, 1877.